The relation between oral health and body mass index among women with hyperthyroidism - Habib kadhom , Eman; Jafer MH. Radhi , Nada (Diyala Journal of Medicine, 2023)
Background: Hyperthyroidism is a medical condition in which excessive synthesis and secretion of thyroid hormones into the blood. According to multiple research, hyperthyroidism is linked to weight loss and increased metabolism. Objective: To assess how hyperthyroidism affects oral health in relation to body mass index. Patients and Methods: The sample was composed of 90 female patients aged 25-45 years include hyperthyroid group and healthy group, the hyperthyroid patients were diagnosed by specialist and under treatment with carbimazole.Clinical evaluation of caries was done according to World Health Organization(2013). The body mass index was measured from the patient’s weight and height, according to the formula World Health Organization(2000). Plaque Index of Silness and Löe was used to evaluate dental plaque (1964),Using the gingival index of Loe and Silness the gingival inflammation was evaluated (1963). Results: Found the Body mass index in the hyperthyroid group was higher than the healthy group with significant difference. The most correlations between caries and body mass index in the hyperthyroid group were weak negative not significant while in the healthy group most correlations were weak positive not significant, the correlations of Gingival index and body mass index were weak positive not significant in both groups.The plaque index had weak negative in hyperthyroid while in control positive correlation and all correlation were not significant. Conclusion: In the present study,the Body mass index higher among women with hyperthyroidism under treatment with carbimazole and the correlation between caries experience and body mass index was negative and not significant.